NANOG promotes cancer stem cell characteristics and prostate cancer resistance to androgen deprivation - Jeter, Collene R. (2011)
Cancer cell molecular mimicry of stem cells (SC) imbues neoplastic cells with enhanced proliferative and renewal capacities. In support, numerous mediators of SC self-renewal have been evinced to exhibit oncogenic potential. We have recently reported that shRNA-mediated knockdown of the embryonic stem cell (ESC) self-renewal gene NANOG significantly reduced the clonogenic and tumorigenic capabilities of various cancer cells. In this study, we sought to test the potential pro-tumorigenic functions of NANOG, particularly, in prostate cancer (PCa). Using quantitative RT-PCR, we first confirmed that PCa cells expressed NANOG mRNA primarily from the NANOGP8 locus on chromosome 15q14. We then constructed a lentiviral promoter reporter in which the -3.8 kb NANOGP8 genomic fragment was used to drive the expression of green fluorescence protein (GFP). We observed that NANOGP8-GFP(+) PCa cells exhibited cancer stem cell (CSC) characteristics such as enhanced clonal growth and tumor regenerative capacity. To further investigate the functions and mechanisms of NANOG in tumorigenesis, we established tetracycline-inducible NANOG overexpressing cancer cell lines, including both prostate (Du145 and LNCaP) and breast (MCF-7) cancer cells. NANOG induction promoted drug-resistance in MCF-7 cells, tumor regeneration in Du145 cells, and, most importantly, castration-resistant tumor development in LNCaP cells. These pro-tumorigenic effects of NANOG were associated with key molecular changes, including an upregulation of molecules such as CXCR4, IGFBP5, CD133 and ALDH1. The present gain-of-function studies, coupled with our recent loss-of-function work, establish the integral role for NANOG in neoplastic processes and shed light on its mechanisms of action.